The Influence Of Giving Fermented Coffee Waste Flour In Rations N Super Kampung Chicken Carcass Production 10 Weeks Of Age - I Gusti Agus Maha Putra Sanjaya; Luh Suariani; Ni Luh Adelia Darma Prakerti Prakerti (Warmadewa University Press, 2024)
Livestock in Indonesia is currently experiencing very rapid development. This development is also accompanied by the increasing need for meat as a source of protein. One source of protein, especially native chicken. An increase in population size and poultry meat production levels needs to be balanced with an increase in feed availability. Super native chickens need quality feed for nutritional fulfillment in order to get optimal results. But the reality faced by farmers today is that the price of commercial feed on the market is very expensive. Feed ingredients that need to be used as alternative feed ingredients include agricultural industry waste, one of which is coffee skin. The purpose of this study was to determine the effect of giving coffee skin flour on the variable production of super-native chicken carcasses until the age of 10 weeks. The experimental design used was a Complete Randomized Design (RAL) consisting of 5 treatments and 3 repeats. The treatment is K0 (ration without the addition of fermented coffee skin flour), K1 (ration containing 3% fermented coffee skin flour.), K2 (ration containing 6% fermented coffee skin flour), K3 (ration containing 9% fermented coffee skin flour), and K4 (ration containing 12% fermented coffee skin flour). The results showed that the addition of fermented coffee skin flour in the ration did not have a noticeable effect (P>0.05) on all observed variables (cutting weight, carcass weight, carcass percentage, and non-carcass percentage). Giving fermented coffee skin flour as much as K3 (9%) absolute gives low cut weight and carcass weight results. While the variable percentage of carcass absolute showed the highest result in the K3 treatment (9%), and in non-carcass variables showed the lowest result in the K3 treatment (9%). Coffee skin is a corn collector but gives results that are not real on chicken carcasses, therefore it is hoped that there will be further research.